Low-carbon water treatment and resource recovery technology: A brief overview of anaerobic membrane bioreactors (AnMBR) characteristics, applications, and innovations - WEN Hanquan; PAN Yuan; YU Hanqing* (能源环境保护)
Anaerobic membrane bioreactors (AnMBR) technology combines the efficiency of anaerobic biological treatment with the selectivity of membrane technology, ushering in a new era in wastewater treatment. With the increasing global focus on environmental protection and resource recycling, AnMBR technology addresses the low-carbon treatment trend and shows promising prospects in resource recycling. This paper provides an overview of AnMBR principles, operational advantages and current practical applications. It also highlights the technological bottlenecks and economic challenges that AnMBR faces in its application, as well as the latest advances in research. The development and implementation of these novel technologies provide robust support for AnMBR in the wastewater treatments and in promoting a circular economy. Although commercializing AnMBR poses challenges, ongoing scientific research and technological innovation are addressing these issues. The groundbreaking progress of AnMBR in enhancing wastewater treatment efficiency, reducing carbon emissions, and fostering the sustainable use of energy and resources heralds a shift towards a greener and more efficient trajectory in water treatment technology. These achievements not only optimize wastewater treatment processes but also contribute significantly to advancing global environmental protection efforts, carrying profound implications for the future management of water resources and environmental conservation.